AI-GENERATED DREAMS: HOW MACHINES ARE SHAPING HUMAN IMAGINATION - Xojabekova , Ramzida (Scientific practical conference, 2026)
This article explores the emerging field of AI-generated creative outputs, often described as “AI-generated dreams,” and their influence on human imagination. It examines the underlying technologies, including neural networks, generative adversarial networks (GANs), and transformer-based models, which enable machines to create novel visual, musical, and narrative content. The paper further analyzes the cognitive, cultural, and societal implications of AI-driven creativity, highlighting both the opportunities and ethical challenges it presents. Case studies from visual arts, music composition, and literature illustrate how AI can augment human creativity and foster collaborative innovation. The article concludes by considering the future trajectory of AI in shaping imaginative processes and the philosophical questions it raises about authorship, originality, and the nature of human creativity.